Sovereign Debt Restructurings 1950-2010. - Trebesch, Christoph (IMF Working Papers., 2012)
This paper provides a comprehensive survey of pertinent issues on sovereign debt restructurings, based on a newly constructed database. This is the first complete dataset of sovereign restructuring cases, covering the six decades from 1950-2010; it includes 186 debt exchanges with foreign banks and bondholders, and 447 bilateral debt agreements with the Paris Club. We present new stylized facts on the outcome and process of debt restructurings, including on the size of haircuts, creditor participation, and legal aspects. In addition, the paper summarizes the relevant empirical literature, anal.